1995
DOI: 10.1063/1.868568
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic study and weakly nonlinear analysis at the onset of Rayleigh–Bénard convection in Hele–Shaw cell

Abstract: The aim of this paper is the derivation of the Ginzburg–Landau equation [as introduced by A. C. Newell and J. A. Whitehead, J. Fluid Mech. 38, 279 (1969)] from the hydrodynamic equations for an infinite Hele–Shaw cell. The dimensional analysis and the asymptotic study allow one to distinguish two nonlinear formulations, each one depends on the order of magnitude of the Prandtl number. The first formulation corresponds to the case Pr=O(1) or Pr≫1, whereas the second corresponds to the case Pr=O(ε*2), where ε*≪1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…They found that for low Prandtl number fluids, modulations in gravity and temperature produce the same flow field both in structure and in magnitude. Clever et al [8], Aniss et al [9,10], Rogers et al [11], Bhadauria et al [12] showed that the gravitational modulation, which can be realized by vertically oscillating a horizontal liquid layer, acts on the entire volume of liquid and may have a stabilizing or destabilizing effect depending on the amplitude and frequency of the forcing. Boulal et al [13] focused attention on the influence of a quasi-periodic gravitational modulation on the convective instability threshold.…”
Section: Introductionmentioning
confidence: 99%
“…They found that for low Prandtl number fluids, modulations in gravity and temperature produce the same flow field both in structure and in magnitude. Clever et al [8], Aniss et al [9,10], Rogers et al [11], Bhadauria et al [12] showed that the gravitational modulation, which can be realized by vertically oscillating a horizontal liquid layer, acts on the entire volume of liquid and may have a stabilizing or destabilizing effect depending on the amplitude and frequency of the forcing. Boulal et al [13] focused attention on the influence of a quasi-periodic gravitational modulation on the convective instability threshold.…”
Section: Introductionmentioning
confidence: 99%
“…In the Hele-Shaw approximation, the order of magnitude of the Prandtl number Pr in the system of equations (4)- (8) has been discussed in [29]. In what follows, we distinguish two different formulations depending on the order of magnitude of the Prandtl number.…”
Section: Asymptotic Study and Stabilitymentioning
confidence: 99%
“…To introduce a perturbation parameter involving only the aspect ratio of the cell, ǫ, we perform a dimensional analysis by means of an appropriate choice of scales used in convection problems in Hele-Shaw cell [29]. Thus, the time is scaled by d 2 /κ, the coordinates (x, y, z) are scaled…”
Section: Formulationmentioning
confidence: 99%
“…Under these assumptions and as in the traditional HeleShaw flow, where the aspect ratio of the cell is considered smaller than unity, a first approximation of the base flow, [17,18], is obtained from the system of equations (1)- (2) as follows…”
Section: Base Flow Solutionmentioning
confidence: 99%